Sosialisasi Bahaya Judi Online dan Pinjaman Online Ilegal di Sekolah Menengah Atas: Pentingnya Kesadaran Sejak Dini: Socialization of the Dangers of Online Gambling and Illegal Online Loans in High Schools: The Importance of Early Awareness - Annisa, Nur; Rozikin, Achmad Zainul; Arafat, Arafat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The rapid development of information technology has a significant impact on every aspect of life, including the emergence of one of the disturbing phenomena of online gambling and illegal online loans. Online gambling offers fantastic winnings that make victims addicted, while illegal online loans offer easy disbursement of funds that trap victims in financial problems. To increase awareness from an early age about the dangers of online gambling and illegal online loans, socialization activities were carried out for students of SMA Negeri-2 Palangka Raya. This socialization used an interactive lecture method with an audio-visual approach, case studies, simulations, and interactive quizzes. The results of the socialization showed that participants experienced an increase in understanding of the modus operandi and legal consequences of online gambling and illegal online loans and built critical awareness. In addition, participants also received education about the importance of wise financial management strategies as a preventive measure.